Psychometric properties of a brief non-verbal test of g factor intelligence - Anunciação, Luis; Marques, Louise; Murray, Christopher; Portugal, Anna C; Rabelo, Ivan; Landeira-Fernandez, Jesus; Cruz, Roberto (Utan Kayu Publishing, 2024)
Intelligence is the most studied construct in psychology and cognitive neuroscience. In Brazil, the administration of intelligence tests is needed for a number of social rights, including driving privileges. Such requirements have led to a large testing industry but the vast majority of intelligence tests require extended administration times and language skills. In this study, we sought to investigate the psychometric properties and normative results of a new non-verbal intelligence test, the General Matrix of Intelligence (GMI). The GMI is comprised of 28 matrix-based items and can be administered in as little as six-minutes. In this initial pilot test, the GMI was administered to 1,326 participants, ages 15-64 years old (M = 25.65 years, SD = 9.6 years), from all regions in Brazil. These data were analyzed using a 2PL Item Response Theory model, regression analyses were conducted to determine the role of sociodemographic factors, and preliminary norms were computed. Results indicated a unidimensional solution that reproduced the g factor theory, invariance across genders, evidence that cognitively demanding items involving movement or three-dimensional shapes were more difficult than items with less cognitive load, a normal distribution for results, and an interaction between education level and age group in predicting performance. Implications of these findings for research and practice are discussed and all data and codes are provided at https://osf.io/kvu42/